Study of economic impact of terminals type A and weigh stations management handover in East Java province to the central government - Anwar, M. Ruslin; Hasyim, M. Hamzah; R. D. A, Ayu (Civil and Environmental Science Journal (CIVENSE), 2019)
Purpose of this study is to know the operational performance of terminals type A and weigh stations in East Java Province, analyse the economic contribution to the regional government, assessing the operational impact terminals type A and weigh, and examine the strategy of minimizing the operational impact if terminals are taken over by the central government. Analysis used in this study are growth analysis, efficiency analysis, ImportancePerformance Analysis (IPA) method, and Strength Weakness Opportunity Threat method. The operational economic performance of Terminals Type A (Arjosari Terminal), obtained retribution of 2,346,495,500 IDR and Bayuangga Terminal obtained retribution of 1,796,877,000 IDR. The operational economic performance of weigh stations is 35,668,880,000 IDR. The operational economic contribution of Terminals Type A and weigh stations is very small/less. The operational impact of Terminals Type A that taken over by the Central Government for the next 15 years is still considered good. Strategy to minimize the operational impact of Terminals Type A with: 1. Strategy S-O (Strength-Opportunity), 2. Strategy S-T (Strength-Threat), 3. Strategy W-O (Weak-Opportunity), 4. Strategy W-T (Weak-Threat). For weigh stations we cannot do IPA and SWOT analysis because all samples of weigh bridges are no longer operating when this study is conducted.